Structural and Luminescent Peculiarities of Spark PlasmaSintered Transparent MgAl2O4 Spinel Ceramics Doped withCerium Ions; Inorganics; Vol. 10, iss. 10 - Valiev D. T. Damir Talgatovich; Stepanov S. A. Sergey Aleksandrovich; Paygin V. D. Vladimir Denisovich; Khasanov O. L. Oleg Leonidovich; Dvilis E. S. Edgar Sergeevich; Lin Chaolu (2022, 2022)
Title screen